541 Investigating myeloid derived suppressor cells (MDSCs) and oligonucleotide based targeting of STAT3 in renal cell carcinoma. (9th November 2020) - Alcantara, Marice; Moreira, Dayson; Hung, Chia-Yang; ,; Wang, Dongfang; Hsu, JoAnn; Pal, Sumanta; Kortylewski, Marcin
Abstract : Background: Recent advancements in the treatment of renal cell carcinoma (RCC) using immune checkpoint inhibitors (ICI) against PD1 or CTLA-4 receptors have improved survival rates in patients. However, more than half of RCC patients does not respond to anti-PD-1/-CTLA-4 combination immunotherapy. Thus, we decided to investigate mechanisms underpinning the resistance to ICI at the cellular and molecular levels. Methods: We utilized multicolour flow cytometry and Luminex assays to investigate patient peripheral blood and used syngeneic mouse models to determine the efficacy of oligonucleotide based targeting of STAT3 Results: First, we characterized immunosuppressive myeloid cell populations, T cell subsets and immune biomarkers in blood samples from RCC patients with advanced stage IV disease, undergoing anti-PD-1/-CTLA-4 (nivolumab/ipilimumab) combination therapy. Results of our multicolor flow cytometry and plasma analysis suggested that ICI therapy is associated with a significant almost 15-fold increase of polymorphonuclear MDSCs (PMN-MDSCs) in the peripheral blood of RCC patients over the course of 3 therapeutic cycles. Notably, we found that PMN-MDSCs showed high levels of activated Signal Transducer and Activator of Transcription 3 (pSTAT3) and a significant increase its downstream target Arginase-I between cycle 1 and cycle 8 of treatment (P=0.0008). The pSTAT3/ARG-1 signaling is known for promoting tumor immune evasion, thus strongly suggesting that immature PMN-MDSCs are potentially involved in limiting outcome of ICI therapy in RCC patients similar as shown before in other genitourinary cancers such as prostate and bladder cancers. We recently developed a strategy to target STAT3 selectively in tumor-associated myeloid cells using using STAT3 antisense oligonucleotide (STAT3ASO) conjugated to immunostimulatory CpG oligodeoxynucleotides acting as targeting moiety. In our initial efficacy studies, we assessed activity of three versions of CpG-STAT3ASO conjugates with various chemical modifications, such as 2'-O'methyl- or locked nucleic acid, in a syngeneic bladder tumor model (MB49). MB49 cancer cells were subcutaneously injected into two flanks of male C57BL/6 mice and treated every second day with 5 mg/kg of various CpG-STAT3ASO injected intratumorally into one of the tumor sites. All CpG-STAT3ASOs inhibited tumor cell growth in both treated and distant tumors in comparison to controls. The immunohistochemical analysis indicated an increase in the percentage of CD8+ T cell with reduction of regulatory T cells within CpG-STAT3ASO treated tumors in comparison to controls, suggesting activation of CD8 T cell-mediated antitumor immunity. Conclusions: Overall, our preliminary results suggest that immune suppressive pSTAT3+/ARG-1+ PMN-MDSCs accumulate in patients with RCC undergoing ICI combination therapy, which may potentially contribute to resistance to ICIs. Targeting STAT3 signaling in the RCC-associated myeloid cells using CpG-STAT3ASO may provide a potential novel strategy for augmenting immune checkpoint therapies.